The placement of a nominee director as controlling mechanism in venture capital financing - Mohammad, Hisham; Minai, Mohd Sobri; Lucky, Esuh Ossai-Igwe (IDOSI Publications, 2014)
The high level of investment risk combined with the absence of collateral have made many venture capitalists to perform thorough evaluation process, establishing full information disclosure and implementing strict monitoring activities during the post investment stage.However, the absence of representatives in the investee firms' boards gives great impact on all the venture capitalists' endeavours to protect their investment interests, exposing them to the possibility of having management conflict and agency problem with their investee firms. As a result, this study investigates the moderating effect of nominee director on the relationship between venture capitalists and their investee firms in venture cooperation.Due to this, a cross-sectional study of questionnaire survey research design was conducted.The questionnaires were distributed through mailing procedure and data was generated from 35 Malaysian venture capital companies. Overall, the findings indicate that the nominee director insignificantly influence the relationship between venture capitalists and their investees in venture cooperation. Further results show that controlling mechanism through the placement of a nominee director failed to moderate the influence of Deal Origination and Screening (DOS), Evaluating Venture Proposal (EVP), Contracting and Deal Structuring (CDS), Monitoring and Post Investment Activities (MPI) and Risk Management (RM) on the management conflict. Based on the findings, it is inferred that venture relationship between venture capitalists and their investee firms are not influenced by the nominee director placed in the investee firms' board. Thus, the study recommends that Malaysian venture capitalists, which include policy makers, to give more consideration to the controlling factor in order to reduce the possibility of conflict to occur in venture cooperation.